2015
DOI: 10.1186/s12916-015-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of statin therapy on mortality in patients with sepsis-associated acute respiratory distress syndrome (ARDS) depends on ARDS severity: a prospective observational cohort study

Abstract: BackgroundPrevious investigations have presumed a potential therapeutic effect of statin therapy in patients with acute respiratory distress syndrome (ARDS). Statins are expected to attenuate inflammation in the lungs of patients with ARDS due to their anti-inflammatory effects. Clinical investigations of the role of statin therapy have revealed contradictory results. This study aimed to investigate whether pretreatment and continuous therapy with statins in patients with sepsis-associated ARDS are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 38 publications
1
59
2
1
Order By: Relevance
“…Neutrophil migration could be rescued in vitro by simvastatin during LRTI and CAP, but not during a severe septic event and not in young donors. This might support the use of high-dose simvastatin preemptively or early during an infective insult in the elderly, but it suggests that a lack of efficacy would be seen in patients with established severe sepsis, corroborating data from interventional trials (12). In vitro chemotaxis findings were replicated for fMLP in the interventional trial in OH adults without impeding other vital neutrophil functions, such as phagocytosis and NET release.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Neutrophil migration could be rescued in vitro by simvastatin during LRTI and CAP, but not during a severe septic event and not in young donors. This might support the use of high-dose simvastatin preemptively or early during an infective insult in the elderly, but it suggests that a lack of efficacy would be seen in patients with established severe sepsis, corroborating data from interventional trials (12). In vitro chemotaxis findings were replicated for fMLP in the interventional trial in OH adults without impeding other vital neutrophil functions, such as phagocytosis and NET release.…”
Section: Discussionsupporting
confidence: 52%
“…3-Hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) lower cholesterol, but some population studies and clinical trials have suggested survival benefits during infection (12). Predosing with statins improves outcomes in murine models of sepsis (13).…”
mentioning
confidence: 99%
“…Major characteristics of the included studies are summarized in Table . In general, the 13 studies, including four RCTs and nine cohort studies, were published between 2007 and 2015 covering a total of 12 145 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective observational study, Mansur and colleagues found that the protection afforded by statin therapy in ARDS was only observed in those patients with severe ARDS. [34] In addition to lower ARDS severity, the SAILS trial also had a relatively low mortality rate amongst patients with severe ARDS at baseline (23.7%). Surprisingly, in the SAILS trial, 60-day mortality was highest in the mild ARDS population (44/145, 30.3%).…”
Section: Discussionmentioning
confidence: 99%